USM TO ENROL 3,700 STUDENTS IN FIRST DEGREE PROGRAMMES FOR 2016/2017 ACADEMIC YEAR - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 8 August 2016 Universiti Sains Malaysia (USM) is expected to enrol about 3,700 students in its fulltime first degree programmes for the upcoming 2016/2017 academic year in all its campuses, which will start on 28 August.